PENGARUH MEDIA PEMBELAJARAN BERBASIS ADOBE ANIMATE TERHADAP HASIL BELAJAR IPAS MATERI SEPERTI APAKAH BUDAYA DAERAHKU SISWA KELAS V DI SD NEGERI 2 LAMBHEU - Muhammad Fazril; Mislinawati; Nurmasyitah; Rauzah (Jurnal Pesona Dasar, 2026)
This research is motivated by the low learning outcomes of students in regional culture and the lack of use of interactive digital learning media in the learning process. This study aims to determine the effect of Adobe Animate-based learning media on the science learning outcomes of fifth-grade students at Lambheu 2 Public Elementary School SD Negeri 2 Lambheu in the subject "What is My Regional Culture Like?". This study used a quantitative approach with a quasi-experimental design and a nonequivalent control group design. The research sample consisted of two classes: class VA as the experimental class with 17 students and class VB as the control class with 19 students. Data collection techniques were carried out through pretests and posttests in the form of multiple-choice questions. Data were analyzed using the N-Gain Score test, the Shapiro-Wilk normality test, the Levene's homogeneity test, and the Independent Samples T-Test hypothesis test using SPSS version 32. The results showed that the average posttest score for the experimental class was 87.05 with an N-Gain of 0.68, while the control class obtained an average posttest score of 77.36 with an N-Gain of 0.43. The Independent Samples T-Test obtained a significance value of 0.001 < 0.05, indicating a significant effect of the use of Adobe Animate-based learning media on students' social studies learning outcomes. Thus, Adobe Animate-based learning media has been proven to significantly influence student learning outcomes in regional culture. This media can also be an innovative alternative for teachers in creating more interactive and engaging learning.